Ethical approaches in contemporary German-language literature and culture - Jeremiah, Emily; Matthes, Frauke (Boydell & Brewer, 2013)
There has been an "ethical turn" in the literature, culture, and theory of recent years. Questions of morality are urgent at a time of increasing global insecurities. Yet it is becoming ever more difficult to make ethical judgments in multicultural, relativist societies. The European economic meltdown has raised further ethical difficulties, widening the gap between rich and poor. Such divisions and difficulties heighten the widespread fear of "the other"in its various manifestations. And in the German context especially, the past and its representation offer ongoing moral challenges. These ethical concerns have found their way into recent German-language literature and culture in texts that deal with history and memory (Timm, Petzold, Schoch, Strubel); materiality (Krau, Overath); gender (Berg, Schneider); age and generation (Moster, Pehnt, Schalansky); religion, especially Islam (Senocak, Kermani, Ruete); and nomadism (Tawada). The relationship between self and other; the connection between particular and general; the personal and political consequences of individuals' actions; and the potential, and danger, of representation itself are issues that are vital to the shaping of our future ethical landscapes, as this volume demonstrates. Contributors: Monika Albrecht, Angelika Baier, David N. Coury, Anna Ertel & Tilmann KoÌ<<ppe, Emily Jeremiah, Alasdair King, Frauke Matthes, Aine McMurtry, Gillian Pye, Kate Roy. Emily Jeremiah is Senior Lecturer in German at Royal Holloway, University of London. Frauke Matthes is Lecturer in German at the University of Edinburgh